Library service enhancement for differently abled undergraduates at University of Kelaniya, Sri Lanka: A review of project - Warnasooriya, T.; Munasinghe, M.A.K.S. (University of Jaffna, 2022)
The library, University of Kelaniya, has given special attention to ensuring the equal provision of facilities for differently abled undergraduates. Accordingly, a service enhancement project was initiated to encourage them to visit the library, access the physical collection and gain a first-hand experience. Accordingly, audio-visual cubicles were established to encourage the library usage of differently abled under graduates. The users were facilitated with a braille book collection, together with a management system, CD and cassette collection, and on-demand reading service, which consisted of 568 items, both lending and reference materials. The collections were searched from the access points of author, title, ISBN, and subject headings. Further, a bilingual searching facility was enabled. CD and cassettes can be played at the given cubicles during library opening hours. A trained library staff member was available for on-demand reading service. The printed books were issued from the lending or reference section. Further, e-resources were read for the users’ requests. In the project’s next phase, the selected recommended readings authored by the University Academics will be converted into a braille document. The project enabled the library to play the role of facilitator to provide equal provision for all users.
Keywords: Differently abled undergraduates; University libraries; Service enhancement; Library projects